How do figurative languages reflect the cultural values in Toba Batak Saur Matua Ceremony - Tampubolon, Marlina; Rakasiwi, Rani; Silalahi, Masriani Mery Rosmida; Siahaan, Ricki Asi Erwindo (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The aims of this study are to describe how do figurative languages reflect the cultural values in Toba Batak Saur Matua Ceremony. This research was conducted by using qualitative descriptive design. The data were the utterances gathered from umpasa that are delivered by Hula-hula, boru, and dongan tubu of 3 Toba Batak saur matua ceremonies in Rantau prapat and Tarutung. The data analyzed by using theory of descriptive analysis. It began from identifying the data that are needed for this research, classifying the data based on the theory of figures of speech and analyzing the data based on the theories that were used. The findings are (1) there were 7 out of 10 kinds of figure of speech were found in the umpasa of Toba Batak saur matua ceremony which were simile, metaphor, personification, symbol, allegory, overstatement/hyperbole, and irony, (2) The most dominant figure of speech in Toba Batak saur matua ceremony was simile (3) Toba Batak people tent to deliver umpasa through simile which compared between two dissimilar things by using the comparative term (like, as) and described to the first qualities of the second of invest the first with connotations inherent in the other. In addition, the figures of speech which were uttered by the speakers such as Hula-hula, boru, and dongan tubu used in Toba Batak saur matua ceremony as a blessing.